Plastic wood, preparation method thereof and application of plastic wood in preparation of acoustic materials
By delectin treatment and epoxy soy acrylic impregnation of the logs, plastic wood with improved flexibility and plasticity was prepared, and honeycomb film acoustic materials were prepared in combination with EVA film, which solved the shortcomings of existing plastic wood and sound insulation materials, and achieved efficient noise isolation and the application of environmentally friendly materials.
Patent Information
- Application Number
- CN202510317238.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-18
- Publication Date
- 2025-04-25
AI Technical Summary
The existing plastic wood has insufficient flexibility and plasticity, complex preparation process and high cost, and traditional sound insulation materials have a large self-weight and poor low-frequency dissipation ability, which pollutes the environment and endangers human health.
After removing lignin from the log, soaking it in epoxy soybean acrylate solution and then soaking it in water, destroying the crystalline form of wood fibers and increasing porosity, thereby preparing plastic wood with significantly improved flexibility and plasticity. At the same time, a honeycomb film acoustic material is used to form plastic wood and ethylene-vinyl acetate copolymer (EVA) film to make up for the shortcomings of traditional sound insulation materials.
The flexibility and plasticity of plastic wood have been significantly improved, with simple process and low cost, suitable for industrial production. Honeycomb film acoustic materials have good sound insulation performance and show excellent sound insulation in the medium and low frequency bands. They are low in density, environmentally friendly, lightweight and high-strength, which can effectively reduce noise and improve riding comfort.
Smart Images

Figure CN119871620A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of wood modification, and in particular, relates to plastic wood and a preparation method thereof and application thereof in the preparation of acoustic materials. Background Art
[0002] Traditionally, the preparation of structural functional materials usually relies on organic polymers (such as plastics) and metals (such as aluminum alloys), which are 3D shaped by extrusion, molding, forging, casting, extrusion, injection molding, etc. to give them a specific shape and rigidity. However, these materials have many limitations in terms of sustainability, environmental friendliness, and biodegradability. In recent years, with the increasing demand for sustainable materials, plastic wood, as a new type of bio-based material, has gradually become a research hotspot due to its unique processability and environmental protection characteristics.
[0003] In the prior art, [Shaoliang Xiao, et al. 2021. "Lightweight, Strong, Moldable Wood via Cell Wall Engineering as a Sustainable Structural Material." Science 374 (6567): 465-469.] Professor Hu Liangbing of the University of Maryland, USA, after decomposing the lignin component of the wood and closing the ducts and fiber gaps by evaporating water, partially re-expanded the wood with a rapid water shock process, selectively opened the duct channels, and formed a unique wrinkled cell wall structure, which provides space for compression and the ability to support high strain, making the material easy to fold and shape, and can achieve different shapes and structures, such as preparing honeycomb core materials. However, this method requires multiple steps, including partial delignification, evaporating water to close ducts and fibers, and a rapid water shock process to partially re-expand the wood. These steps increase the complexity and cost of processing, limiting its large-scale industrial application. [Zhou, X., et al. 2023. "Shape and Stiffness Switchable Hydroplastic Wood with Programmability and Reproducibility." ACS Nano.] Based on the cell wall wetting modification and drying process, Professor Zhou Xiaoyan directly converted natural thick wood into hydroplastic wood with high mechanical strength and shape adjustability, and successfully programmed hydroplastic wood with different reversible 2D / 3D shapes to achieve the processability of wood shape and adjustability of stiffness. However, the preparation process of hydroplastic wood involves steps such as cell wall wetting treatment, softening and multiple dehydration. The process is relatively complicated and will lead to high production costs. The shape and stiffness adjustment of hydroplastic wood depends on the absorption and evaporation of water, so its performance will be affected in high humidity or extremely dry environments.
[0004] Although the preparation method of plastic wood has application potential, it still faces problems such as complex process, high cost, and poor environmental adaptability in practical applications. The existing plastic wood lacks flexibility and plasticity, and there is a lack of discussion on fine processing and molding. The design and application of the structure are also insufficient. It cannot adapt to a variety of flexible material application scenarios and needs further optimization and improvement.
[0005] In recent years, with the development of industrialization, noise pollution has become increasingly serious. Therefore, the research and promotion of sound insulation materials has become one of the main research directions in the field of acoustic research. Research in the field of acoustic materials can help solve traditional noise pollution and hinder the spread of various types of noise. However, the existing traditional sound insulation materials have problems such as being too heavy to be updated, poor dissipation of low-frequency sound waves, or polluting the environment and endangering human health. They cannot meet people's demand for green sound insulation materials in the context of health and environmental protection.
[0006] Acoustic metamaterials, a new material proposed at the beginning of this century, provide new possibilities for the control and application of sound through sophisticated microstructure design. [Yingli Li, Yonglin Zhang, Suchao Xie, 2020. A lightweight multilayer honeycomb membrane acoustic metamaterial. Applied Acoustics] Li and other researchers have developed a lightweight multilayer honeycomb thin film acoustic metamaterial, and verified the excellent performance of the material in terms of sound transmission loss through theoretical analysis and experiments, but its sound absorption frequency band is relatively narrow, and it is difficult to cover a wider frequency range. In addition, the design and manufacturing process of the material is relatively complicated, and the arrangement and parameters of the microstructure units need to be precisely controlled, which increases the manufacturing cost and difficulty. Therefore, a new acoustic material is urgently needed to solve the above problems. Summary of the invention
[0007] 1. Problems to be solved
[0008] Aiming at the technical problems that the existing plastic wood has insufficient flexibility and plasticity, and the preparation process is complicated and the cost is high, the present application provides a preparation method of plastic wood, and the plastic wood obtained by modifying natural wood material has significantly improved flexibility and plasticity.
[0009] At the same time, in view of the technical problems that the acoustic materials in the prior art are too heavy to be updated, have poor dissipation capacity for low-frequency sound waves, pollute the environment, and endanger human health, this application also provides a method for preparing the acoustic material, using plastic wood and ethylene-vinyl acetate copolymer (EVA) film to form a green honeycomb film acoustic material, which not only meets the performance requirements, but also makes up for the shortcomings of traditional sound insulation materials. This application also provides the application of plastic wood and acoustic materials.
[0010] 2. Technical solution
[0011] In order to achieve the above purpose, the technical solution provided is:
[0012] The method for preparing plastic wood comprises the following steps:
[0013] Delignifying the logs to obtain pretreated wood;
[0014] The pretreated wood is immersed in an epoxy soy acrylate solution, wherein the concentration of the epoxy soy acrylate is 10wt% to 40wt%, to obtain immersed wood;
[0015] The impregnated wood is immersed in water to obtain plastic wood.
[0016] Preferably, the solvent in the epoxy soy acrylate solution is acetone.
[0017] Preferably, the logs are taken out and rinsed until the remaining water on the surface is neutral.
[0018] Preferably, the drying is performed after the lignin is removed, the drying is freeze drying, the freezing time is 48 hours, and the drying is performed in a vacuum freeze drying box.
[0019] Furthermore, the impregnation is carried out under vacuum, and the impregnation time is 12 hours to 24 hours.
[0020] Furthermore, a delignification solution is used to remove lignin, wherein the delignification solution is a mixed solution containing sodium hydroxide and sodium sulfite, and the molar ratio of the sodium hydroxide to the sodium sulfite is 2-3:0.2-0.5.
[0021] Furthermore, the time for removing lignin is 6h to 12h, and the temperature is 80°C to 100°C.
[0022] Furthermore, the log is any one of balsa, basswood, pine, birch or poplar.
[0023] The plastic wood is prepared by the preparation method of the plastic wood.
[0024] Acoustic material, including the plastic wood.
[0025] The method for preparing the acoustic material comprises the following steps:
[0026] Drying and molding the plastic wood to obtain a wood-based functional material;
[0027] Combining the wood-based functional materials into a honeycomb structure;
[0028] The honeycomb structure is bonded to the film by an adhesive and cured to obtain an acoustic material.
[0029] Preferably, the honeycomb structure is composed of a periodic array of regular hexagonal basic units.
[0030] Furthermore, the film is made of ethylene-vinyl acetate copolymer; and the adhesive is a light-curing adhesive polyethylene glycol diacrylate.
[0031] The application of the plastic wood or the acoustic material is to apply the plastic wood or the acoustic material to the preparation of furniture, construction industry and / or transportation vehicles.
[0032] 3. Beneficial effects
[0033] Compared with the existing known technology, the technical solution provided by the present invention has the following beneficial effects:
[0034] (1) The method for preparing plastic wood of the present invention comprises removing lignin from logs to increase the porosity of the obtained wood; then immersing the logs in an epoxy soy acrylate solution to allow the epoxy soy acrylate to be more evenly filled into the pores; and then soaking the logs in water, where the intrusion of water and epoxy soy acrylate destroys the crystal form of the wood fibers, causing separation and slippage between the fibers, thereby improving the flexibility and plasticity of the obtained plastic wood. The plastic wood can be processed into various shapes by mechanical bending, folding, twisting, etc. without breaking the fibers, and the method is simple in process, low in cost, and easy to industrialize.
[0035] (2) Compared with logs, the plastic wood of the present invention has significantly improved flexibility and plasticity. The moldable wood, i.e., the plastic wood, can be processed into various shapes by mechanical bending, folding, twisting, etc. without fiber breakage; the dimensional stability of the plastic wood of the present application is improved by 80%.
[0036] (3) The acoustic material of the present invention uses plastic wood that is obtained by modifying natural wood, which is an environmentally friendly material; it has a low density and a small mass per unit volume; it has high mechanical properties and can maintain structural integrity and function under large external forces. The sound insulation effect is achieved in the medium and low frequency bands, which is in line with experimental expectations. On the basis of meeting the acoustic performance requirements of the sound insulation material, it makes up for the shortcomings of common sound insulation materials; the sound insulation performance of the three-layer honeycomb film acoustic material is equivalent to that of 30mm thick polyurethane foam or 2mm thick steel plate (the mass is 5 times that of the honeycomb film acoustic material).
[0037] (4) The preparation method of the acoustic material of the present invention is to combine the plastic wood into a honeycomb structure through dry molding. The honeycomb structure is composed of a periodic array of basic units of regular hexagons, and has the characteristics of environmental protection, light weight, high strength, etc. The honeycomb structure can withstand 769.2 times its own weight pressure; the honeycomb structure and EVA film are combined to make a honeycomb film acoustic material. This composite structure utilizes the light weight and energy absorption characteristics of the honeycomb structure, as well as the flexibility and damping characteristics of the EVA film, and can better isolate low-medium-low frequency noise; the EVA film has good weather resistance and anti-aging properties, and can protect the honeycomb structure from moisture and corrosion. This composite material can still maintain stable acoustic performance under complex environmental conditions; the combination of the honeycomb structure and the EVA film can be achieved by a simple bonding or hot pressing process, and the processing technology is simple and the cost is low. In addition, this composite material can also be cut and spliced according to actual needs, and is easy to install.
[0038] (5) Application of the plastic wood and acoustic material of the present invention. Plastic wood and acoustic materials prepared based on the plastic wood are widely used in the construction field due to their good sound absorption and sound insulation properties. These materials can be used for interior decoration, such as walls, ceilings and floors, and can effectively control the indoor reverberation time, improve sound quality, and enhance speech clarity. They also have important applications in noise control of transportation vehicles such as cars, trains and airplanes. These materials can effectively reduce wind noise, road noise and mechanical noise, and improve ride comfort. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 Schematic diagram of the preparation of moldable wood and acoustic materials of the present application;
[0040] Figure 2 This is a physical diagram of the single-layer structure of the acoustic material of this application;
[0041] Figure 3 This is a schematic diagram of the acoustic material structure assembly of this application;
[0042] Figure 4 is a comparison of the flexibility of different materials, a1, b1, c1 and d1 are the crease images of logs, wood with partial removal of lignin and hemicellulose, impregnated wood and moldable wood after folding; a2, b2, c2 and d2 are SEM images of the folded parts of the above corresponding materials;
[0043] Figure 5 Demonstration diagram of shaping method for moldable wood;
[0044] Figure 6 The figure is a comparison of the shrinkage and swelling rates of wood (MW10, MW20, MW30 and MW40) impregnated with epoxy soy acrylate solution of different concentrations and the same type of products (DW);
[0045] Figure 7 This is a diagram showing the load-bearing capacity of honeycomb film acoustic materials;
[0046] Figure 8 This is the sound insulation test diagram of honeycomb film acoustic material;
[0047] Fig. 9 These are the sound insulation test diagrams of single-layer, double-layer and triple-layer honeycomb film acoustic materials. DETAILED DESCRIPTION
[0048] In order to further understand the content of the present invention, the present invention is described in detail in conjunction with embodiments.
[0049] The experimental raw materials, reagents and instruments used in the preparation methods of the plastic wood and acoustic materials in the following examples are as follows:
[0050] Table 1 Experimental materials and reagents
[0051]
[0052] Table 2 Experimental instruments list
[0053]
[0054] Other common instruments used in the experiment include beakers, measuring cylinders, glass rods, weighing bottles, medicine spoons, tweezers, etc.
[0055] Example 1
[0056] The method for preparing the plastic wood and acoustic material of this embodiment comprises the following steps:
[0057] S1. Process balsa wood (Ochroma lagopus Swartz) to 80 mm × 10 mm × 0.5 mm (longitudinal × radial × tangential), immerse in a delignification solution for 9 hours at a temperature of 80°C to obtain wood from which lignin and hemicellulose are partially removed; take out the wood from which lignin and hemicellulose are partially removed from the delignification solution, rinse with water until the rinsed water is neutral when measured with a pH test paper, to obtain rinsed wood; wrap the rinsed wood with tin foil and freeze it for 48 hours, and then put the frozen wood into a vacuum freeze dryer to dry it, to obtain pretreated wood;
[0058] Preparation method of delignification solution: mix sodium hydroxide and sodium sulfite in a molar ratio of 2.5:0.4, add water, put into an oil bath pot and heat until solid particles disappear to form a uniform and transparent mixed solution, i.e., delignification solution.
[0059] The balsa wood is first immersed in a delignification solution to obtain wood with some lignin and hemicellulose removed, at which point the porosity of the wood increases; then it is rinsed with water to effectively remove the chemical substances remaining on the surface or inside of the wood, preventing them from having adverse effects on subsequent processing or use, and to clean the residues in the pores, making the pore structure of the wood more transparent; then the water in the wood is frozen at low temperatures through freeze drying, and then the ice is directly sublimated into water vapor under vacuum conditions, thereby avoiding the collapse of the pore structure caused by capillary tension during the evaporation of water. This method can better preserve the microscopic pore structure of the wood, while reducing the deformation and dimensional changes of the wood during the drying process. This allows the wood to maintain good dimensional stability and mechanical properties after drying.
[0060] S2, placing the pretreated wood in parallel and without overlapping into the epoxy soy acrylate solution and applying vacuum, and immersing for 24 hours under a negative pressure of 0.1 MPa to obtain impregnated wood;
[0061] Preparation method of epoxy soy acrylate solution: dissolve epoxy soy acrylate in acetone solution, stir until solid disappears, and the concentration of epoxy soy acrylate is 10wt%;
[0062] S3, taking out the impregnated wood from the epoxy soy acrylate solution, and soaking it in water for 10 minutes to obtain a moist moldable wood, i.e., a moldable wood;
[0063] Plastic wood has strong flexibility and plasticity. It can be processed into various shapes through mechanical bending, folding and twisting without fiber breakage. When the external force is removed, the wood maintains this deformation and will not return to its original shape.
[0064] The pretreated wood is immersed in an epoxy soy acrylate solution to allow the epoxy soy acrylate to fill the pores more evenly; then it is soaked in water. The intrusion of water and epoxy soy acrylate destroys the crystalline morphology of the wood fibers, causing separation and slippage between the fibers, thereby improving the flexibility and plasticity of the obtained plastic wood.
[0065] S4, placing the obtained wet moldable wood in a mold and molding it in a dry manner to obtain a wood-based functional material; combining the wood-based functional material into a honeycomb structure, wherein the honeycomb structure is composed of a periodic array of basic units of regular hexagons, such as Figure 3 As shown, the basic unit of the regular hexagon has a side width of 0.1 mm and a vertical thickness of 2 mm;
[0066] By removing moisture through drying, the fibers are reconnected, thereby playing a shaping role; the honeycomb structure has high strength and rigidity while maintaining lightness. The honeycomb structure can effectively absorb and isolate sound waves. The hexagonal pores inside can prevent air flow, thereby hindering the propagation of sound waves and achieving good sound absorption effects.
[0067] S5. The honeycomb structure is bonded to the film by an adhesive, wherein the film is made of ethylene-vinyl acetate copolymer (EVA); the adhesive is a light-curing adhesive polyethylene glycol diacrylate, and the mass ratio of polyethylene glycol diacrylate to epoxy soy acrylate is 1:500; the bonded whole is then placed in a UV curing box for curing for 30 seconds to obtain a honeycomb thin film acoustic material with a thickness of 2 mm and a diameter of 10 cm, such as Figure 2 and Figure 3 shown.
[0068] The honeycomb structure and EVA film are combined to make the honeycomb film acoustic material. This composite structure utilizes the lightweight and energy absorption characteristics of the honeycomb structure and the flexibility and damping characteristics of the EVA film to effectively isolate low, medium and low frequency noise. The EVA film has good weather resistance and anti-aging properties, and can protect the honeycomb structure from moisture and corrosion. This composite material can still maintain stable acoustic performance under complex environmental conditions.
[0069] Schematic diagram of the preparation of plastic wood and acoustic materials Figure 1 shown.
[0070] Example 2
[0071] The method for preparing the plastic wood and acoustic material of this embodiment comprises the following steps:
[0072] S1. Process balsa wood (Ochroma lagopus Swartz) to 80 mm × 10 mm × 0.5 mm (longitudinal × radial × tangential), immerse in a delignification solution for 9 hours at a temperature of 80°C to obtain wood from which lignin and hemicellulose are partially removed; take out the wood from which lignin and hemicellulose are partially removed from the delignification solution, rinse with water until the rinsed water is neutral when measured with a pH test paper, to obtain rinsed wood; wrap the rinsed wood with tin foil and freeze it for 48 hours, and then put the frozen wood into a vacuum freeze dryer to dry it, to obtain pretreated wood;
[0073] Preparation method of delignification solution: mix sodium hydroxide and sodium sulfite in a molar ratio of 2.5:0.4, add water, put into an oil bath pot and heat until solid particles disappear to form a uniform and transparent mixed solution, i.e., delignification solution.
[0074] S2, placing the pretreated wood in parallel and without overlapping into the epoxy soy acrylate solution and applying vacuum, and immersing for 24 hours under a negative pressure of 0.1 MPa to obtain impregnated wood;
[0075] Preparation method of epoxy soy acrylate solution: dissolve epoxy soy acrylate in acetone solution, stir until solid disappears, and the concentration of epoxy soy acrylate is 20wt%.
[0076] S3. Take the impregnated wood out of the epoxy soy acrylate solution and soak it in water for 10 minutes to obtain moist moldable wood, i.e., moldable wood.
[0077] S4, placing the obtained wet moldable wood in a mold and molding it in a dry manner to obtain a wood-based functional material; combining the wood-based functional material into a honeycomb structure, wherein the honeycomb structure is composed of a periodic array of regular hexagonal basic units, and the regular hexagonal basic unit has a side width of 0.1 mm and a vertical thickness of 2 mm;
[0078] S5. The honeycomb structure is bonded to a membrane by an adhesive to form a whole, wherein the membrane is made of ethylene-vinyl acetate copolymer; the adhesive is a light-curing adhesive polyethylene glycol diacrylate, and the mass ratio of polyethylene glycol diacrylate to epoxy soy acrylate is 1:500; the bonded whole is then placed in a UV curing box for curing for 30 seconds to obtain a honeycomb thin film acoustic material with a thickness of 2 mm and a diameter of 10 cm.
[0079] Example 3
[0080] The method for preparing the plastic wood and acoustic material of this embodiment comprises the following steps:
[0081] S1. Process balsa wood (Ochroma lagopus Swartz) to 80 mm × 10 mm × 0.5 mm (longitudinal × radial × tangential), immerse in a delignification solution for 9 hours at a temperature of 80°C to obtain wood from which lignin and hemicellulose are partially removed; take out the wood from which lignin and hemicellulose are partially removed from the delignification solution, rinse with water until the rinsed water is neutral when measured with a pH test paper, to obtain rinsed wood; wrap the rinsed wood with tin foil and freeze it for 48 hours, and then put the frozen wood into a vacuum freeze dryer to dry it, to obtain pretreated wood;
[0082] Preparation method of delignification solution: mix sodium hydroxide and sodium sulfite in a molar ratio of 2.5:0.4, add water, put into an oil bath pot and heat until solid particles disappear to form a uniform and transparent mixed solution, i.e., delignification solution.
[0083] S2, placing the pretreated wood in parallel and without overlapping into the epoxy soy acrylate solution and applying vacuum, and immersing for 24 hours under a negative pressure of 0.1 MPa to obtain impregnated wood;
[0084] Preparation method of epoxy soy acrylate solution: dissolve epoxy soy acrylate in acetone solution, stir until solid disappears, and the concentration of epoxy soy acrylate is 30wt%.
[0085] S3. Take the impregnated wood out of the epoxy soy acrylate solution and soak it in water for 10 minutes to obtain moist moldable wood, i.e., moldable wood.
[0086] S4, placing the obtained wet moldable wood in a mold and molding it in a dry manner to obtain a wood-based functional material; combining the wood-based functional material into a honeycomb structure, wherein the honeycomb structure is composed of a periodic array of regular hexagonal basic units, and the regular hexagonal basic unit has a side width of 0.1 mm and a vertical thickness of 2 mm;
[0087] S5. The honeycomb structure is bonded to a membrane by an adhesive to form a whole, wherein the membrane is made of ethylene-vinyl acetate copolymer; the adhesive is a light-curing adhesive polyethylene glycol diacrylate, and the mass ratio of polyethylene glycol diacrylate to epoxy soy acrylate is 1:500; the bonded whole is then placed in a UV curing box for curing for 30 seconds to obtain a honeycomb thin film acoustic material with a thickness of 2 mm and a diameter of 10 cm.
[0088] Example 4
[0089] The method for preparing the plastic wood and acoustic material of this embodiment comprises the following steps:
[0090] S1. Process balsa wood (Ochroma lagopus Swartz) to 80 mm × 10 mm × 0.5 mm (longitudinal × radial × tangential), immerse in a delignification solution for 9 hours at a temperature of 80°C to obtain wood from which lignin and hemicellulose are partially removed; take out the wood from which lignin and hemicellulose are partially removed from the delignification solution, rinse with water until the rinsed water is neutral when measured with a pH test paper, to obtain rinsed wood; wrap the rinsed wood with tin foil and freeze it for 48 hours, and then put the frozen wood into a vacuum freeze dryer to dry it, to obtain pretreated wood;
[0091] Preparation method of delignification solution: mix sodium hydroxide and sodium sulfite in a molar ratio of 2.5:0.4, add water, put into an oil bath pot and heat until solid particles disappear to form a uniform and transparent mixed solution, i.e., delignification solution.
[0092] S2, placing the pretreated wood in parallel and without overlapping into the epoxy soy acrylate solution and applying vacuum, and immersing for 24 hours under a negative pressure of 0.1 MPa to obtain impregnated wood;
[0093] Preparation method of epoxy soy acrylate solution: dissolve epoxy soy acrylate in acetone solution, stir until solid disappears, and the concentration of epoxy soy acrylate is 40wt%.
[0094] S3. Take the impregnated wood out of the epoxy soy acrylate solution and soak it in water for 10 minutes to obtain moist moldable wood, i.e., moldable wood.
[0095] S4, placing the obtained wet moldable wood in a mold and molding it in a dry manner to obtain a wood-based functional material; combining the wood-based functional material into a honeycomb structure, wherein the honeycomb structure is composed of a periodic array of regular hexagonal basic units, and the regular hexagonal basic unit has a side width of 0.1 mm and a vertical thickness of 2 mm;
[0096] S5. The honeycomb structure is bonded to a membrane by an adhesive to form a whole, wherein the membrane is made of ethylene-vinyl acetate copolymer; the adhesive is a light-curing adhesive polyethylene glycol diacrylate, and the mass ratio of polyethylene glycol diacrylate to epoxy soy acrylate is 1:500; the bonded whole is then placed in a UV curing box for curing for 30 seconds to obtain a honeycomb thin film acoustic material with a thickness of 2 mm and a diameter of 10 cm.
[0097] In other embodiments, the plastic wood may be made of basswood, pine, birch or poplar.
[0098] Comparison of the flexibility of different materials, such as Figure 4 As shown, a1 is the folded crease image of balsa log, b1 is the folded crease image of wood with some lignin and hemicellulose removed, c1 is the folded crease image of wood impregnated in Example 3, and d1 is the folded crease image of moldable wood in Example 3; a2, b2, c2 and d2 are SEM images of the folded parts of the materials corresponding to a1, b1, c1 and d1 respectively. Figure 4 It can be seen that balsa logs, wood with partial removal of lignin and hemicellulose, and wood after impregnation all had fiber breakage after folding and had no plasticity, while the flexibility and plasticity of moldable wood were significantly improved, and no fiber breakage occurred after folding.
[0099] Mouldable wood shaping methods, e.g. Figure 5As shown, the moldable wood has good plasticity and can be processed into various shapes by mechanical bending, folding and twisting without fiber breakage. When the moldable wood is shaped into the target structure, its shape is fixed by drying, a low-energy method.
[0100] Wood dimensional stability test, in Examples 1-4, epoxy soy acrylate solutions with concentrations of 10wt%, 20wt%, 30wt% and 40wt% were used for impregnation, and the impregnated wood was MW10, MW20, MW30 and MW40, respectively, compared with the shrinkage and swelling rates of the same type of product DW [Shaoliang Xiao, et al. 2021. "Lightweight, Strong, Moldable Wood via Cell Wall Engineering as a Sustainable Structural Material." Science 374 (6567): 465-469.]. Figure 6 As shown, the swelling and shrinkage dimensional change rate of MW30 is about 1 / 5 of that of the same type product DW, and the dimensional stability of the plastic wood of the present application is improved by more than 80%.
[0101] Honeycomb membrane acoustic material load-bearing capacity test, such as Figure 7 As shown, the honeycomb film acoustic material weighing only 1.3g can withstand a weight of 1000g without visible deformation, maintaining structural integrity and function, and having good mechanical properties; the mechanical properties of balsa wood from which lignin and hemicellulose have been partially removed after impregnation and molding with epoxy soy acrylate solution have been improved to a certain extent, with good load-bearing and compressive properties, and the honeycomb structure can withstand a pressure 769.2 times its own weight.
[0102] The sound insulation test of the honeycomb film acoustic material, the sound insulation effect data of the single-layer honeycomb film acoustic material (HC10, HC20, HC30) obtained in Examples 1-3 and the single-layer ethylene-vinyl acetate copolymer film (EVA) are compared, as shown in FIG. Figure 8As shown, the acoustic material with a single-layer honeycomb structure can achieve certain sound insulation performance compared with a single-layer EVA film, and can be used for sound insulation of building walls. When the concentration of the epoxy soy acrylate solution (i.e., the concentration of the impregnation solution) is 30wt%, the impregnation effect is the best. When the concentration of the epoxy soy acrylate solution is increased to 40wt%, the impregnation effect becomes worse due to the decrease in the fluidity of the impregnation solution, and more impregnation solution remains in the beaker. As the concentration of the impregnation solution increases (up to 30wt%), the sound insulation effect of the prepared honeycomb film acoustic material increases. In the 800-1400Hz range, the honeycomb film acoustic material with an impregnation solution concentration of 30wt% exhibits the highest sound insulation performance. The honeycomb film acoustic material of the present application achieves sound insulation effects in the medium and low frequency bands, which is in line with experimental expectations. On the basis of meeting the acoustic performance requirements of the sound insulation material, it makes up for the shortcomings of common sound insulation materials.
[0103] The single-layer, double-layer and triple-layer honeycomb film acoustic materials were tested for sound insulation. The single-layer honeycomb film acoustic material was prepared by Example 1, the double-layer honeycomb film acoustic material was assembled from the single-layer honeycomb film acoustic materials prepared by Examples 2 and 3, and the triple-layer honeycomb film acoustic material was assembled from the single-layer honeycomb film acoustic materials prepared by Examples 1-3. The sound insulation test results are shown in FIG. Fig. 9 As shown, the double-layer and triple-layer sound insulation structures can achieve higher sound insulation and bandwidth, and the sound insulation performance of the three-layer honeycomb film acoustic material is equivalent to that of 30mm thick polyurethane foam or 2mm thick steel plate (the mass is 5 times that of the honeycomb film acoustic material). This multi-layer honeycomb film acoustic structure can be used for sound insulation of building walls or train carriages.
[0104] Comparative Example 1
[0105] The wood preparation method of this comparative example comprises the following steps:
[0106] By using a phenolic resin modifier with a ratio of phenol: formaldehyde: sodium hydroxide of 1.8:1.0:0.2 to in-situ impregnate the wood, the mechanical strength and hardness of the resulting wood are improved, but the flexibility and plasticity of the wood cannot be improved.
[0107] Reference [Li Ping, Zhang Yuan, Wu Yiqiang, et al. Research on phenolic resin modified fir wood based on in-situ impregnation method [J]. Materials Guide, 2021, 35(22): 22193-22199.].
[0108] Comparative Example 2
[0109] The wood preparation method of this comparative example comprises the following steps:
[0110] Using Cs2ZrCl6:Te 4+Modified perovskite transparent wood (epoxy resin impregnated) improves the flexibility of the material, but it is impossible to achieve the effect of folding the wood completely 180 degrees.
[0111] Reference [Chen Luwei. Research on the optical properties of perovskite transparent wood and its building materials properties [D]. Kunming University of Science and Technology, 2023. DOI: 10.27200 / d.cnki.gkmlu.2023.002583.].
[0112] The above-mentioned embodiments only express the preferred implementation modes of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present invention. It should be pointed out that, for a person skilled in the art, several modifications, improvements and substitutions can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the present invention patent shall be subject to the attached claims.
Claims
1. A method for preparing plastic wood, characterized in that: The following steps are involved: Delignifying the logs to obtain pretreated wood; The pretreated wood is immersed in an epoxy soy acrylate solution, wherein the concentration of the epoxy soy acrylate is 10wt% to 40wt%, to obtain immersed wood; The impregnated wood is immersed in water to obtain plastic wood.
2. The method for preparing plastic wood according to claim 1, characterized in that: The impregnation is carried out under vacuum, and the impregnation time is 12 hours to 24 hours.
3. The method for preparing plastic wood according to claim 1, characterized in that: A delignification solution is used to remove lignin, wherein the delignification solution is a mixed solution containing sodium hydroxide and sodium sulfite, and the molar ratio of the sodium hydroxide to the sodium sulfite is 2-3:0.2-0.
5.
4. The method for preparing plastic wood according to claim 3, characterized in that: The time for removing lignin is 6h to 12h, and the temperature is 80℃ to 100℃.
5. The method for preparing plastic wood according to any one of claims 1 to 4, characterized in that: The log is any one of balsa, basswood, pine, birch or poplar.
6. Plastic wood, characterized by: Prepared by the method according to any one of claims 1 to 5.
7. Acoustic material, characterized in that: The plastic wood material comprises the plastic wood material as claimed in claim 6.
8. The method for preparing the acoustic material according to claim 7, characterized in that: The following steps are involved: Drying and molding the plastic wood to obtain a wood-based functional material; Combining the wood-based functional materials into a honeycomb structure; The honeycomb structure is bonded to the film by an adhesive and cured to obtain an acoustic material.
9. The method for preparing the acoustic material according to claim 8, characterized in that: The film is made of ethylene-vinyl acetate copolymer; the adhesive is light-curing adhesive polyethylene glycol diacrylate.
10. Use of the plastic wood according to claim 6 or the acoustic material according to claim 7, characterized in that: The plastic wood or acoustic material is applied in the preparation of furniture, construction industry and / or vehicles.
Citation Information
Cited By
High-strength wood honeycomb and preparation method thereof
CN120439412A